Fundamental study of spermatogenesis in vitro from two types of azoospermic testicular biopsy - Azantee Yazmie binti Abdul Wahab (Kulliyyah of Allied Health Science, International Islamic University Malaysia, 2017)
Azoospermia is a male infertility worldwide concern due to incomplete spermatogenesis process. Recreating spermatogenesis outside of its original environment (in vitro) is a scientific curiosity in andrology world. However, it remains challenging due to the limitation of culture system. Testicular biopsy cells from non-obstructive azoospermia (NOA) (complete absence of spermatozoa) and obstructive azoospermia (OA) (obstruction in the male ducts results in absence of spermatozoa in semen) patients were obtained to develop in vitro spermatogenesis. Modified human embryonic stem cells (HESC) media using knockout DMEM and knockout serum replacement were used to determine growth factors (basic fibroblast growth factor (BFGF) and leukemia inhibitory factor (LIF)) that were suitable for the development of spermatogenic cells. In the early phase of study, NOA sample was selected to see the potential development of spermatogonial stem cells (SSCs). The sample was cultured in HESC medium with BFGF. Protein markers; ITGA6, ITGB1, GFRA6 and CD9 were done using immunofluorescent staining on Day 1, 7, 14 and 21 but non of the markers were present, only unknown cells has been detected. Cultures were then extended until Day 49 using both NOA and OA samples. Each sample divided into two groups; HESC with BFGF and HESC with LIF. OCT4, ITGA6, ITGB1, GFRA6 and CD9 markers were positive in immunofluorescent staining and quantitative reverse transcriptase polymerase chain reaction (qRT-PCR) indicated the SSC-like cells development in both NOA and OA samples. Both of the culture samples were extended until 90 days and most of the azoospermia samples had successfully developed post-meiotic cell specified spermatid-like cells except NOA sample cultured with HESC and BFGF that shown unknown cells detected. This revealed that late spermatogenesis could be established in vitro using HESC or in vitro fertilization (IVF) media with the addition of reproductive hormones (follicle stimulating hormone (FSH) and testosterone). SCP3, H2B and TP1 markers were positive indicating that meiotic division has occurred in the culture. This study managed to show some evidence of in vitro spermatogenesis. It opens of possibilities to create spermatozoa in the future, thus giving hope to azoospermic especially NOA patients to have biological children.